Improving strategic decision making with big data-based media analysis - the case of coal power. (30th September 2019) - Nuortimo, Kalle; Harkonen, Janne
Big-data based methods are developed to aid corporate decision-making. This study utilises big-data based global media-analysis to clarify the role of coal-power related media-image in company decision-making. Opinion mining by a specific software tool for media-analysis and monitoring is utilised. The analysis bases on the notion that the media-image of company products - or specific technologies - may impact corporate investment and divestment decisions in the energy sector. The assumption is that coal-power related media-image may cause corporate brandimage pressures. The findings indicate that the general media-sentiment towards coal-power is negative, possibly influencing corporate decisions. The large negative media-sentiment towards coal-power may override the benefits of developing cleaner coal-power and related technologies such as carbon capture and storage and utilisation. The negative media-sentiment towards coal-power may mitigate the more positive image of related less-known technologies. Evidence is provided on the media-impact of coal-power related divestment decisions and potential impacts on decision making.